The Role of Autologous Stem-Cell Transplantation in High-Risk Neuroblastoma Consolidated by anti-GD2 Immunotherapy. Results of Two Consecutive Studies - Mora, Jaume; Castañeda, Alicia; Flores, Miguel A.; Santa-María, Vicente; Garraus, Moira; Gorostegui, Maite; Simao, Margarida; Perez-Jaume, Sara; Mañe, Salvador (Frontiers in Pharmacology, 2020)
Background: Treatment of HR-NB comprise induction, consolidation with autologous stem cell transplant (ASCT) followed by anti-GD2 immunotherapy and isotretinoin. Childrens Oncology Group and SIOPEN studies used dinutuximab and cytokines to treat patients in complete remission or refractory Bone/Bone marrow (B/BM) disease after ASCT. Methods: HR-NB patients referred to Hospital Sant Joan de Déu for anti-GD2 immunotherapy were eligible for two consecutive studies (dinutuximab for EudraCT 2013–004864–69 and naxitamab for 017–001829–40) and naxitamab/Sargramostim CU with or without prior ASCT. Patients enrolled in first complete remission or with primary refractory B/BM disease. We accrued a study population of two groups whose therapy, aside from ASCT, was similar. This is a retrospective analysis of their outcome calculated from study entry. Results: From December 2014–2019, 67 patients were treated with dinutuximab and cytokines (n = 21) in the Hospital Sant Joan de Déu-HRNB-Ch14.18 study or with naxitamab and Sargramostim either in the Ymabs study 201 (n = 12) or CU (n = 34). 23 patients were treated with primary refractory disease in the B/BM (11 with dinutuximab and 12 with naxitamab), and 44 in first CR (10 with dinutuximab and 34 with naxitamab). Study patients included 13 (19.4%) treated following single ASCT and 54 following conventional chemotherapy. Median follow-up for all patients is 16.2 months. Two-year rates for ASCT and non-ASCT patients were, respectively, EFS 64.1% vs. 54.2% (p = 0.28), and OS 66.7% vs. 84.1% (p = 0.81). For the 44 pts in first CR, 2-years rates for ASCT and non-ASCT patients were, respectively, EFS 65.5% vs. 58.7% (p = 0.48), and OS 71.4% vs. 85.4% (p = 0.63). Conclusions: In this retrospective, single center study, ASCT did not provide survival benefit when anti-GD2 immunotherapy was used after induction chemotherapy.